Masjid : Sejarah Singkat, Komponen dan Konteks Regional - Effendi Nurzal; Faiza Aidina (Bayt ElHikmah: Journal of Islamic Architecture and Locality, 2023)
Abstract. The mosque is a public building and one of the architectural forms of Islamic culture. There have been numerous studies discussing mosques, including historical studies, analyses of stylistic forms, thermal comfort, circulation, and other aspects. Due to the multitude of research variations, this article aims to re-explore the foundational knowledge of mosques. It begins by delving into the origins of mosques and their brief history, the initial mosque prototypes, their relationship with the building's components, and the evolution of their architecture in relation to regional contexts. This research falls within the realm of qualitative research, employing data collection techniques from several literature sources. The findings indicate that the history and prototypes of early mosques (influenced by pre-Islamic styles) played a significant role in the overall architectural development of mosques worldwide. However, regional contexts introduce new dimensions to the appearance and impression of mosques. What remains unchangeable is the foundation of Islamic religion, which serves as the primary reference in determining policies related to the architectural development of mosques.